Leaf detective: using evidence of damage on mangrove leaves to measure the effects of different herbivores. (2nd January 2020) - Davidson, Timothy M.; Sokoloski, Chasmin; Smith, Celia M.
Abstract: Herbivores are important to ecosystems because they transfer energy stored in plant matter to other organisms. However, when herbivores occur in high abundances, they can become pests and harm the plants that form the basis of food webs. Mangroves are saltwater tolerant trees found along most tropical and subtropical shorelines. Because mangroves live between land and sea, a wide range of herbivores and other organisms, such as pathogens and parasites, affect them. Many of these organisms leave distinctive marks on the leaves that they eat or infect; scientists can use those marks to help identify the organisms that caused the damage. In this activity, students will take on the role of "Leaf Detectives" and examine patterns of leaf damage on red mangrove leaves ( Rhizophora mangle ) to infer which organism(s) are harming the mangroves on fictional Lobster Island. Students will collect data from their sample leaves, summarize the results with a graph, and then make a conclusion based on the scientific evidence. By classifying and measuring different damage patterns on leaves, students will learn how different organisms affect plants and food webs, develop pattern recognition skills, and practice using the scientific method to make evidence-based conclusions.